Facts about Consumption of Counterfeit Products (NonOriginal) - Edy Purwo Saputro; Irmawati Irmawati; Mabruroh Mabruroh; Dewi Probowati Setyaningrum (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Consumption of counterfeit products is one of the interesting issues in the marketing field because it is not only related to theoretical but also marketing interests. The purpose of this research is to examine the intention to buy counterfeit products by involving 150 young people in Solo. The analysis shows that value consciousness and social risk affect the purchase intention of counterfeit products, while the perceived risk variable has no effect.